2015
DOI: 10.1001/jamaoncol.2014.206
|View full text |Cite|
|
Sign up to set email alerts
|

Use of Electric Power Morcellation and Prevalence of Underlying Cancer in Women Who Undergo Myomectomy

Abstract: The prevalence of cancers and precancerous abnormalities of the uterus in women who undergo myomectomy with or without electric power morcellation is low overall, but risk increases with age. Electric power morcellation should be used with caution in older women undergoing myomectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 36 publications
0
44
1
Order By: Relevance
“…Of the suggested risk factors for sarcoma, it is notable that none of the women we identified were post-menopausal, exposed to pelvic radiation or tamoxifen, nor had a family history of cancer. The average age of women undergoing hysterectomy at our institution was younger than that in the Michigan study, and our finding of a relatively young cohort of women with sarcoma is unexpected and contrary to expectations of age-related risks (13,21). The absence of these risk factors may be related to why these patients were not referred to gynecologic oncologists and were not suspected to have sarcomas preoperatively.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Of the suggested risk factors for sarcoma, it is notable that none of the women we identified were post-menopausal, exposed to pelvic radiation or tamoxifen, nor had a family history of cancer. The average age of women undergoing hysterectomy at our institution was younger than that in the Michigan study, and our finding of a relatively young cohort of women with sarcoma is unexpected and contrary to expectations of age-related risks (13,21). The absence of these risk factors may be related to why these patients were not referred to gynecologic oncologists and were not suspected to have sarcomas preoperatively.…”
Section: Discussioncontrasting
confidence: 70%
“…Furthermore, mixed populations including women undergoing hysterectomy and myomectomy were used to derive the risk estimate, and some studies also included referral patients which may have elevated the risk. This methodology may have additional flaws since the indications for myomectomy are different from those for hysterectomy, and thus the populations, age distribution, and incidence of occult malignancy in the two groups vary (20,21). Though many of the studies used by the FDA in their pooled analysis were from university hospitals and referral centers much like ours, they were not able to describe clinically relevant factors such as preoperative evaluation and postoperative care and outcomes (18).…”
Section: Discussionmentioning
confidence: 92%
“…In total, we identified 20 studies that examined the prevalence of occult uterine cancers in patients with presumed benign disease. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] In total, 12 studies were limited to patients with presumed uterine leiomyomas as the only surgical indication and were included in the primary results, [22][23][24][25][26][28][29][30][31][32][33]37 whereas the remainder included other gynecologic surgical indications in addition to uterine fibroids. [18][19][20][21]27,[34][35][36] Of the 12 studies limited to patients with presumed uterine leiomyomas, only 1 was a prospective observational study, 32 whereas all others were retrospective analyses of individual institutions [22][23][24][25][28]…”
Section: Incidence Of Occult Cancer In Presumed Fibroidsmentioning
confidence: 99%
“…[18][19][20][21]27,[34][35][36] Of the 12 studies limited to patients with presumed uterine leiomyomas, only 1 was a prospective observational study, 32 whereas all others were retrospective analyses of individual institutions [22][23][24][25][28][29][30][31]33 or of population-wide trendsfromastateornationaldatabase. 26,37 Nine of the 12 had study populations of over 1000 patients. [22][23][24][25][26]28,30,31,37 Table 1 displays the study characteristics.…”
Section: Incidence Of Occult Cancer In Presumed Fibroidsmentioning
confidence: 99%
“…11 A number of articles provide varying estimates of the risk of sarcomatous changes in presumptive fibroid uterus, with likely prevalence rates of 0.14% and 0.19%. 12,13 Unfortunately, there is no reliable diagnostic method to differentiate benign from malignant processes in presumptive leiomyoma. A recent meta-analysis of 202 leiomyosarcoma cases revealed that power morcellation, when compared with laparotomy, increased both intra-abdominal recurrence rates (39% compared with 9%; odds ratio 4.11) as well as death rates (48% compared with 29%; odds ratio 2.42), although the literature is still limited.…”
Section: Power Morecellatorsmentioning
confidence: 99%